UJI INHIBITOR ENZIM TIROSINASE EKSTRAK DAN FRAKSI DAUN KEDABU (Sonneratia ovata Backer) SECARA IN-VITRO - Ainun Alfatma; Rahma Dona; Armon Fernando; Fina Aryani; Rahayu Utami; Septi Muharni; Husnawati; Wira Noviana Suhery; Melzi Octaviani; Mustika Furi (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Kedabu leaves (Sonneratia ovata Backer) are known contain secondary metabolites, one of which is phenolic, flavonoid and antioxidant activity. Phenolic, flavonoids and antioxidant are known to inhibit the tyrosinase enzyme. The tyrosinase enzyme is involved in the process of melanogenesis which produces melanin. Melanin can cause hyperpigmentation. To prevent hyperpigmentation, tyrosinase inhibitors are needed. This study aimed to test the tyrosinase enzyme inhibitor in ethanol extract, n-butanol fraction, ethyl acetate fraction, n-hexane fraction of kedabu leaf (Sonneratia ovatta Backer) using L-tyrosine as a substrate. The method used to get ethanol extract using ethanol maceration, while some fractions are obtained using the fractionation method. The test was carried out using L-tyrosine and kojic acid as a positive control with absorption measurements using microplate reader at a wavelength of 492 nm. The results showed that the best tyrosinase inhibitory activity was produced by the ethyl acetate fraction with an IC50 value of 18,82 g/mL, followed by the n-butanol fraction with an IC50 value of 24,42 g/mL, and the n-hexane fraction with an IC50 value. 28,77 g/mL, ethanol extract with an IC50 value of 99,09 with a strong category for all samples compared with kojic acid as a positive control with an IC50 value of 30,09 g/mL.